Physical and Thermodynamic Properties of Poly(2-phenyl-1,3-dioxolane-4-yl-methyl-methacrylate-coethylmethacrylate) Polymer with Inverse Gas Chromatography - HAMDI KARAGOZ, M.; ERGE, HASAN; ILTER, ZULFIYE (Asian Journal of Chemistry, 2010)
In this study, the physical and thermodynamic properties of poly(2- phenyl-1,3-dioxolane-4-yl-methyl-methacrylate-co-ethylmethacrylate) (PDMMA-EM) were investigated by using inverse gas chromatography. Two groups of alcohols and alkanes with different chemical natures and polarities were used to obtain some properties of (PDMMA-EMsolvent) systems. The specific retention volume, Vg0, glass transition temperature, Tg, the sorption enthalpy, ΔH1S, sorption free energy, ΔG1S, sorption entropy, ΔS1S, the weight fraction activity coefficients of solute probes at infinite dilution, Ω1∞ and Flory-Huggins interaction parameters, χ12∞, between polymer and solvents were determined in the temperature range of 333-473 K. The solubility parameters of PDMMA-EM at infinite dilution was also found by plotting the graph of [δ12 - (ΔG1∞/V1)] versus solubility parameters, δ1, of probes.